Organomineral fertilizer from sewage sludge: nutrient recycling and environmental safety for tropical agriculture - Rodrigues, Mayra Maniero (2023)
The proper disposal of sewage sludge (SS) is one of the great challenges for the sustainability of modern society. This material is a rich source of organic matter and nutrients for plants. However, its use in agriculture is associated with high concentrations of heavy metals such as Zn and Ni, at levels that may make its application in the soil unfeasible. In this sense, the use of SS in the synthesis of organomineral fertilizers (SS-OMF) is a promising strategy that allows aligning the proper disposal of SS with improvements in soil fertility and reduction of dependence on mineral fertilizers (MFs), mainly in tropical agriculture. Our objective was to explore the effects of an SS-OMF formulation on soil-plant-microorganisms and to understand possible synergistic and inhibitory effects of the mineral and organic mixture on tropical agroecosystems. A critical literature review based on bibliometric analysis was carried out to understand the state of the art on SS-OMFs between 2012-2023, potentialities, and gaps regarding its synthesis and use as an alternative to the exclusive use of SS in crops. Tropical agriculture has great potential for using this fertilizer, in Brazil, due to the presence of weathered soils, with low levels of organic matter and micronutrients, which demand large amounts of external inputs. Then, we proposed the synthesis and characterization of an SS-OMF 4-8-8 in three physical forms (powder, granule, and pellet) and evaluated its agronomic potential and environmental safety. The final product obtained was free of pathogenic agents, had safe levels of heavy metals, and met the requirements established by legislation for agricultural use. A field study was carried out in which the SS-OMF, in the three physical forms, was applied at two rates (70% and 100% of the P2O5 soybean requirement) and compared to an MF in a soybean maize off-season succession system in no-tillage in the Brazilian Cerrado area. Compared to SS, the application rate of SS-OMF is 3.5 times lower, due to the higher concentration of nutrients, which favors transport operations and application in the field. Our main findings indicate that, in the first year of application in soybeans, SS-OMF favors plant nodulation, mainly granules, and pellets, compared to the use of powder and MF. Regardless of the physical form, agronomic responses, heavy metal contents in soil-plant, and effects on soil quality bioindicators were equivalent between SS-OMF and MF, both for soybean and maize. The residual effect on maize off-season was greater with the use of an equivalent rate to MF, with the pellet\'s physical form being interesting. We believe that this holistic approach encourages sustainable management strategies in tropical agriculture, combining environmental sustainability and productivity gains.